PERBUATAN MELAWAN HUKUM OLEH OKNUM PETUGAS MEDIS PT.KIMIA FARMA DALAM PENGGUNAAN SWAB TEST ANTIGEN BEKAS - Amanda Nadya Oktavia (2022)
The Indonesian government in an effort to suppress the spread of the Covid-19 virus has made several efforts, one of which is by making a policy for people who will travel by air in which prospective passengers are required to show negative evidence of the RT-PCR swab test or antigen swab test. The high consumer demand for swab test services has even been misused by unscrupulous medical officers at PT. Kimia Farma Diagnostics at Kualanamu International Airport by recycling and reusing medical device consumers, namely dacron swabs in antigen swab test services. The research method used by the author is a type of normative juridical research using a law approach, a case approach, and a conceptual approach. This study aims to answer the formulation of the problem, namely how is the juridical analysis in the use of used antigen swab devices by medical personnel and what legal remedies are carried out by consumers who use used antigen swab test services. Based on the results of the research, unscrupulous medical officers have violated the law as regulated in Article 1365 of the Civil Code, Article 196 of the Health Law, Article 62 paragraph (1) of the Consumer Protection Law, Article 55 paragraph (1) of the 2nd Criminal Code and Article 65 paragraph (1) KUHP. Legal efforts made by consumers are through litigation by reporting to the North Sumatra Police until they have reached an inkracht decision in which individual medical officers are proven to have violated Article 196 of the Health Law jo. Article 55 Paragraph (1) number 2 of the Criminal Code jo. Article 65 Paragraph (1) of the Criminal Code.